La pénétration économique en Amérique latine - Donneur, André (Études internationales, 1983)
In 1970, Canada decided to develop its relations with Latin America, especially in the economic sector. Adhesion to the Interamerican Bank of Development and the status of observator in the Organisation of American States was a good institutional basis for increasing these relations. However, the absence of objectives on refugee and immigration questions prevented adoption of a clear policy towards Chilian and Haitian refugees. Generally Canada had met the 1970 objectives. Trade increased substantially, partly as a result of Canadian policies, but also because of the development of the main countries: Brazil, Mexico and Venezuela and the increase in oil prices. It could be more important if vigourous policies were implemented. Canada has important investments in Latin America, especially in Brazil. In percentage of total Canadian aid, aid to Latin America declined from 1970. Relations with Latin America will increase during the 1980's, but they would be more important if Canada adopted a more coherent policy.